Utilization of AI In Reorienting Digital Da’wah Based On Religious Moderation to Address Religious Consumerism Among Generation AI: A Qur’anic Perspective - Maulida; Robby Aditya Putra (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study explores the integration of artificial intelligence (AI) into digitally moderated Islamic da’wah to prevent consumerism among Generation AI from a Qur’anic perspective. Using a qualitative approach and literature review, it examines the potential of AI to expand the reach and effectiveness of Islamic messages through features such as interactive chatbots, content personalization, recommendation algorithms, big data analysis, and virtual assistants. The findings indicate that AI can support a more adaptive, moderate, and secure form of da'wah, while also serving as a tool for training preachers and preventing the spread of extremist content. Additionally, AI plays a crucial role in detecting and countering extremist narratives and enhancing the effectiveness of message delivery by da'wah practitioners. From a Qur’anic perspective, AI can align with the principles of moderation emphasized in the Qur'an. Wasatiyyah (moderation) is central in Surah Al-Baqarah [2:143]. The Qur'an also highlights the importance of avoiding excess and materialism, such as in Surah At-Takathur [102:1], which resonates with the study’s aim to use AI to address the excessiveness of religious consumerism in the digital age. With AI, digital da'wah can become more responsive and uphold the values of moderation, ensuring that Islamic teachings remain relevant, accessible, and grounded in balance and restraint. Theoretically, this study enriches the literature on AI integration in Islamic da'wah, while deepening the understanding of moderation (wasatiyyah) in modern technology. Practically, it offers strategic guidelines for developing relevant and transformative AI-based digital da'wah content that aligns with Islamic values.